Visualizing Changing Landscapes: Disappearance of the Scioto Lobe of the Laurentide Ice Sheet, Ohio. A Field Guide - Leavell, Daniel; Angle, Mike; Mark, Bryan G.; Howat, Ian (Byrd Polar Research Center, The Ohio State University, 2010)
This field trip guide was produced for participants of the International Glaciological Society Symposium, “Earth’s Disappearing Ice: Drivers, Responses and Impacts,” which was held at the Byrd Polar Research Center in August 2010. The field trip began at Ohio State University in Columbus and continued to Licking County, including stops in Granville, Alexandria, St. Louisville and Newark. Landforms associated with the Scioto Lobe of the Laurentide Ice Sheet (LIS) in east central Ohio during the Last Glacial Maximum (LGM) reveal the processes, materials and environments of the glacier system. The authors reconstruct the paleogeography and glacial history to provide a model of changes at and near the ice margin on this glaciated section of the Appalachian Plateaus Province at 40°N. In eastern Licking County, kames, terraces, moraines, ice-marginal lake deposits and reversed drainage systems record the impact of the glacier at and beyond the terminus. Field stops highlight glacial, glacifluvial, and glacilacustrine landforms and related materials (e.g. till, outwash gravel, lake sediments and peat deposits). International Glaciological Society